2015
DOI: 10.4049/jimmunol.1500689
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Development, and Function of Uterine Innate Lymphoid Cells

Abstract: Innate lymphoid cells (ILCs), including NK cells, contribute to barrier immunity and tissue homeostasis. In addition to the role of uterine NK cells in placentation and fetal growth, other uterine ILCs (uILCs) are likely to play roles in uterine physiology and pathology. In this article, we report on the composition of uILCs in the endometrium during the luteal phase and in the decidua during early pregnancy. Whereas nonkiller uILC1s and uILC2s are barely detectable in mouse and not detected in humans, a sizea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
188
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(204 citation statements)
references
References 45 publications
13
188
0
Order By: Relevance
“…When assayed ex vivo, these decidual NK cells have low lytic activity but are characterized by secretion of cytokines and chemokines that may shape the decidual vasculature during pregnancy. Similarly, NK cells, as well as ILC1s, ILC2s and ILC3s, are found in the uterine tissues of mice 16 .…”
Section: Properties Of Nk Cellsmentioning
confidence: 85%
“…When assayed ex vivo, these decidual NK cells have low lytic activity but are characterized by secretion of cytokines and chemokines that may shape the decidual vasculature during pregnancy. Similarly, NK cells, as well as ILC1s, ILC2s and ILC3s, are found in the uterine tissues of mice 16 .…”
Section: Properties Of Nk Cellsmentioning
confidence: 85%
“…While cNK cells depend on NFIL3 for development, trNK cells in the liver, skin, kidneys, and uterus develop mostly independently of NFIL3 (3, 10). It was also recently reported that salivary gland NK cells develop entirely independently of NFIL3 activity (22, 23).…”
Section: Resultsmentioning
confidence: 99%
“…Other than uNK cells, first defined in 1991, ILC1s and ILC3s have also been identified in human decidua (2, 33, 69, 70). Uterine ILC3s (uILC3s) were initially classified as stage 3 uNK cell progenitors based upon their CD34 − CD117 + CD94 − CD56 + KIR − phenotype.…”
Section: Uterine Ilcsmentioning
confidence: 99%
“…uNK cells in mice can now be classified as CD49a + DX5 +/− uterine tissue-resident NK (trNK) cells and CD49a − DX5 + uterine conventional NK (cNK) cell populations (33, 48, 58, 59), which will be described in greater depth later in this review. DBA reactivity is strongest on uterine CD49a + trNK, and is weak on DX5 + uterine cNK (40, 58).…”
Section: Introductionmentioning
confidence: 99%